BRD4 Mediates Cadmium-Induced Oxidative Stress and Kidney Injury in Mice via Disruption of Redox Homeostasis - Jiaxin Chen; Guangling Guo; Xinyu Wang; Zifa Li; Tingru Ji; You Li; Hongwei Dong; Hao Zhang; Mingzhou Gao (Toxics)
Cadmium (Cd) is a toxic heavy metal that threatens public health, with kidney injury being one of the common manifestations after Cd exposure. Oxidative stress plays a crucial role in Cd-induced kidney injury, arising from an imbalance between cellular oxidation and antioxidation processes. Bromodomain-containing protein 4 (BRD4) has been identified as a significant factor in the initiation and advancement of multiple diseases, primarily due to its regulatory role in oxidative stress. Nevertheless, the specific role of BRD4 in Cd-induced kidney oxidative injury remains poorly understood. The present study demonstrates that BRD4 is activated in the kidney after Cd exposure, while JQ1 (a BRD4 inhibitor) treatment inhibits Cd-induced oxidative stress and kidney injury. Subsequently, we investigate the mechanisms by which Cd regulates oxidative stress both in vivo and in vitro. The results indicate that JQ1 treatment reduces the expression levels of NADPH oxidase 4 (Nox4), thereby alleviating mitochondrial damage and reducing reactive oxygen species (ROS) generation. Furthermore, JQ1 treatment facilitates nuclear translocation levels of Nuclear factor erythroid-derived 2-like 2 (Nrf2), thereby enhancing the antioxidant defense system in the kidney after Cd exposure. In conclusion, this study reveals that BRD4 is significantly involved in the process of Cd-induced oxidative damage in the kidney, while inhibiting BRD4 is observed to attenuate ROS generation by regulating Nox4 and enhance ROS scavenging by regulating Nrf2, which, in turn, suppresses the oxidative stress level in the kidney after Cd exposure. These findings suggest that targeting BRD4 may represent an effective strategy for the prevention and treatment of Cd-induced kidney diseases.